2010
DOI: 10.1097/dad.0b013e3181d68381
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cutaneous Epstein-Barr Virus-Associated T-Cell Lymphoproliferative Disorder-2 Cases With Unusual, Prolonged Clinical Course

Abstract: Hydroa vacciniforme-like lymphoma and extranodal-type natural killer (NK)/T-cell lymphoma are prototypes of Epstein-Barr virus (EBV)-associated cutaneous T- or NK-cell lymphomas. Hydroa vacciniforme-like lymphoma with systemic spread and extranodal-type NK/T-cell lymphoma are characterized by aggressive clinical course. We describe 2 patients with primary cutaneous EBV-associated T-cell lymphomas who did not satisfy the criteria for well-defined entities and showed unusual, prolonged clinical course. They pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…This is reinforced by a recent description by another group of 2 similar cases lacking facial involvement. 44 Overall, these data suggest that the spectrum of cutaneous EBV-positive lymphoproliferative disorders may be larger than initially suspected, also including cases with features of HMB. 29,55 Collectively, these cases could be termed Endemic Childhood Cutaneous NK/T-cell Lymphoma, thereby emphasizing their common distinctive features.…”
Section: Discussionmentioning
confidence: 77%
“…This is reinforced by a recent description by another group of 2 similar cases lacking facial involvement. 44 Overall, these data suggest that the spectrum of cutaneous EBV-positive lymphoproliferative disorders may be larger than initially suspected, also including cases with features of HMB. 29,55 Collectively, these cases could be termed Endemic Childhood Cutaneous NK/T-cell Lymphoma, thereby emphasizing their common distinctive features.…”
Section: Discussionmentioning
confidence: 77%
“…(6)(7)(8)(9) However, the definition of each EBV-associated T/NK LPD is unclear and there is significant overlap between them. (5,(9)(10)(11)(12)(13) Therefore, diagnosis of EBV-associated T/NK LPD can be problematic.…”
Section: Cd8mentioning
confidence: 99%
“…So the latest edition of WHO classification grouped it as one of major types of EBV-positive T-cell lymphoproliferative disorders of childhood, and suggested "HV-like lymphoma" could be a more appropriate classification and descriptive term. 1 We have reviewed HV-like lymphoma reported in the English literature in recent 2 decades [2][3][4][5]8,[10][11][12][13][14] (Table 1). It revealed that all patients were from Asia and South America, especially Korea, Japan, China, and Mexico.…”
Section: Discussionmentioning
confidence: 99%